Faktor-Faktor Yang Mempengaruhi Reputasi Lingkungan Perusahaan Indonesia - Wulan Budi Astuti; Rosida Dwi Ayuningtyas (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
ABSTRACT This study aimed to examine the influence of Corporate Social Responsibility reporting quality and the characteristics of the board of commissioners towards the environment reputation of the company. Samples of study were companies listed on the Indonesian Stock Exchange received a rating in PROPER years 2015-2018. Samples obtained a total of 109 companies. Hypothesis testing is done using a multiple regression analysis with Partial Least Square method. The results showed that Corporate Social Responsibility reporting quality and gender diversity affect the environment reputation of the company, but in a different direction. Corporate Social Responsibility reporting quality positive effect on the company's environment reputation. Gender diversity commissioners negatively affect the company's environment reputation. While the size of the board of commissioners and board committee has no influence on the company's environment reputation. Key words: Environment reputation, CSR reporting, characteristics of the board of commissioners.